Martensitic transformation-induced hydrogen desorption characterized by utilizing cryogenic thermal desorption spectroscopy during cooling. (September 2016) - Koyama, Motomichi; Abe, Yuji; Saito, Kei; Akiyama, Eiji; Takai, Kenichi; Tsuzaki, Kaneaki
Abstract: Hydrogen desorption associated with thermally induced α′ and ε martensitic transformations was characterized by cryogenic thermal desorption spectroscopy (C-TDS) during cooling. The utilization of a cooling process during C-TDS measurements revealed that the dominant factors in the hydrogen desorption related to the α′ and ε martensitic transformations were local changes in diffusivity and motions of transformation dislocations, respectively. Graphical abstract: